1982
DOI: 10.1111/j.1365-2842.1982.tb01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile periodontitis: an historical review

Abstract: A review of the literature on juvenile periodontitis has been undertaken. This paper traces the historical development of the appreciation of the condition. Some of the numerous early attempts to define a systemic background are noted, and the concept of 'periodontosis' and its subsequent influence, e.g. on epidemiological and clinical studies are discussed. The refining over the last 20 years of the concept of aggressive periodontal disease in the young is recorded. The patterns of bone loss in juvenile perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…Previous studies (45) and more recent surveys consistently report low prevalence rates of aggressive periodontitis in Caucasians compared with other race groups. In the 1986/1987 national survey of US schoolchildren, two studies assessed the prevalence of aggressive periodontitis; both reported that the prevalence was highest among Black Americans (2.6% and 2.64%), followed by Hispanic Americans (0.5% and 1.08%), whereas White Americans had the lowest prevalence of aggressive periodontitis (0.06% and 0.17%) (8,36).…”
Section: Race/ethnicitymentioning
confidence: 79%
See 1 more Smart Citation
“…Previous studies (45) and more recent surveys consistently report low prevalence rates of aggressive periodontitis in Caucasians compared with other race groups. In the 1986/1987 national survey of US schoolchildren, two studies assessed the prevalence of aggressive periodontitis; both reported that the prevalence was highest among Black Americans (2.6% and 2.64%), followed by Hispanic Americans (0.5% and 1.08%), whereas White Americans had the lowest prevalence of aggressive periodontitis (0.06% and 0.17%) (8,36).…”
Section: Race/ethnicitymentioning
confidence: 79%
“…children, adolescents and young adults have long been described, and several nomenclatures and classifications have been suggested during the past few decades (12,14,15,20,45). The term 'juvenile periodontitis' was widely used following its introduction in the late 1960s and was later included in the 1989 classification system proposed by the World Workshop in Clinical Periodontics (1).…”
mentioning
confidence: 99%